Faktor-faktor yang mempengaruhi pemilihan karir profesi akuntan publik bagi mahasiswa akuntansi - Esi Wildiana; Taufeni Taufik; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted by using a survey of students in Accounting University of Riau (UR), State Islamic University (UIN), Islamic University of Riau (UIR) in Pekanbaru. This study aims to determine the effect of intrinsic factors of work, financial rewards, consideration of labor market, social values and work environment on career choice public accounting profession.The population in this study were all accounting students who have taken courses audit 1. Samples taken of accounting totaled 94 students. The type of data used is primary data by using questionnaire method of data collection. The method of data analysis used in this study is multiple regression (multiple regression) with the help of SPSS version 17.Results of hypothesis testing showed variable intrinsic factor of work tcount 3.713, ttable 1.986 with a significant value of 0.000, the financial rewards gained tcount 4.334, ttable 1.986 with significant value 0.000 and obtain a work environment tcount 2.649, ttable 1.986 with significant value by 0.010, with the results of the above three variables influence the career choice public accounting profession. . While considerations of labor market variable gain tcount 0.894, ttable 1.986 with significant values of 0.374 and acquire social values of tcount 0.678, ttable 1.986 with a significant value of 0.500, with the results of both these variables did not significantly influence the selection of professional career public accountant. The independent variables in this study were able to influence the dependent variable, while the remaining 38% is explained by other variables not included in this study, such as market motivation, motivation of individual personality, IPK, type of work, number of jobs, students' perceptions of sacrifices and benefits of public accountants , professional training, professional recognition, subjective norms, and perceived behavioral control.Key Word : intrinsic factors of work, financial rewards, consideration of labor market, social values, work environment, career choice public accounting profession